The role of WTAP in regulating macrophage-mediated osteoimmune responses and tissue regeneration in periodontitis - Li, Yuman; Yang, Yue; Niu, Yuting; Li, Yao; Hu, Zhewen; Sun, Shiyu; Chen, Yiming; Hu, Bo; Huang, Ying; Deng, Xuliang (Frontiers in Immunology, 2024)
Periodontitis, delineated by the destruction of structures that support teeth, is predominantly propelled by intricate immune responses. Immunomodulatory treatments offer considerable promise for the management of this ailment; however, the modulation of the periodontal immune microenvironment to facilitate tissue regeneration presents a substantial biomedical challenge. Herein, our study investigates the role of Wilms' tumor 1-associating protein (WTAP), a critical m 6 A methyltransferase, in the immunomodulation of periodontitis and assesses its viability as a therapeutic target. We observed heightened expression of WTAP in macrophages extracted from gingival tissues impacted by periodontitis, with a strong association with M1 polarization. Via lossof-function experiments, we demonstrated that diminishing WTAP expression precipitates a transition from M1 to M2 macrophage phenotypes amidst inflammatory conditions, thus improving the periodontal immune landscape. Further, RNA sequencing and indirect co-culture assays indicated that suppressing of WTAP expression modulates osteoimmune responses and enhances the osteogenic differentiation of bone marrow stromal cells. The local deployment of adeno-associated virus-shWTAP in murine models of periodontitis robustly validated the therapeutic promise of targeting WTAP in this disease. Collectively, our findings highlight the crucial role of WTAP in orchestrating macrophage-mediated osteoimmune responses and tissue regeneration in periodontitis, proposing novel avenues for immunotherapeutic interventions in its treatment.